Contextual factors affecting autonomy for patients in Iranian hospitals: A qualitative study - Hossein Ebrahimi; Efat Sadeghian; Naeimeh Seyedfatemi; Eesa Mohammadi; Maureen Crowley (Wolters Kluwer Medknow Publications, 2016)
Background: Consideration of patient autonomy is an essential element in individualized, patient-centered, ethical care. Internal and external factors associated with patient autonomy are related to culture and it is not clear what they are in Iran. The aim of this study was to explore contextual factors affecting the autonomy of patients in Iranian hospitals. Materials and Methods: This was a qualitative study using conventional content analysis methods. Thirty-four participants (23 patients, 9 nurses, and 2 doctors) from three Iranian teaching hospitals, selected using purposive sampling, participated in semi-structured interviews. Unstructured observation and filed notes were other methods for data collection. The data were subjected to qualitative content analysis and analyzed using the MAXQDA-10 software. Results: Five categories and sixteen subcategories were identified. The five main categories related to patient autonomy were: Intrapersonal factors, physical health status, supportive family and friends, communication style, and organizational constraints. Conclusions: In summary, this study uncovered contextual factors that the care team, managers, and planners in the health field should target in order to improve patient autonomy in Iranian hospitals.